Challenging structures: gender transformative interventions by livestock CRP in Ethiopia - Kinati, Wole; Temple, Elizabeth C.; Baker, Derek; Najjar, Dina (Frontiers in Sustainable Food Systems, 2023)
This study is a review of secondary literature that has been synthesized to extract information and demonstrate the implementation and impact of community conversations (CCs) on gender aspects of social norms in the livestock-based systems in Ethiopia. The study used the phenomenological method of qualitative literature review to sketch the gender transformative approach to delivery of knowledge products in a program on transforming the small ruminant value chain. The CC aimed at addressing gender related norms of division of labor, resource ownership, and handling practices of animals and their products previously identified, and those emerged during the CC events across the study sites. A total of 1517 community members (out of which 574 are women) took part in various CC events. The review shows that the gender related norms addressed were in line with the identified constraining norms faced by women livestock keepers in the mixed and livestock-based systems. The CC approach adopted complied with the stages laid out in literature: identification of existing knowledge; imparting new knowledge; knowledge integration and application; and review, reflection and re-planning. The process was inclusive and community engaging, which possibly cultivated intrinsic motivation, and ownership of the process. Changes in knowledge, attitudes and practices at household, community and institutional levels were identified. Conclusions include institutionalizing the gender transformative approach in the public agricultural extension system. This could be facilitated by generation of robust objective evidence of impacts, and guidance for subsequent scaling at local, regional, and national levels.